2022
DOI: 10.1007/s10792-022-02486-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring association between pseudoexfoliation syndrome and ocular aging

Abstract: Purpose Within a population-based follow-up study, to examine the 10-year incidence of pseudoexfoliation syndrome (PEX), possible risk factors for PEX and its association with ocular aging of the cornea, lens and retina. Methods The baseline examination was conducted in 2006 on a random sample of 1,033 adult participants from Kaunas city (Lithuania) population of whom 631 had ophthalmic examination data at attendance of the 10-year follow-up in 2016. Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Our findings are consistent with previous research, which has demonstrated an age-related increase in the occurrence of cataracts among individuals with PEX syndrome [ 5 , 9 ]. The prevalence was only 0.4% in patients under 50 years of age and 82% in patients over 70 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous research, which has demonstrated an age-related increase in the occurrence of cataracts among individuals with PEX syndrome [ 5 , 9 ]. The prevalence was only 0.4% in patients under 50 years of age and 82% in patients over 70 years.…”
Section: Discussionsupporting
confidence: 93%
“…While PEX syndrome occurs worldwide, its prevalence significantly varies among different geographic regions and different ethnic groups. It is more common in Scandinavian, Mediterranean, and Middle Eastern countries (with a prevalence between 16% and 30%), and less common among the Inuit populations in Greenland, Alaska, and Canada (with a prevalence of 0%) [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…XFS is an age-related disorder characterized by an excess of extracellular matrix, particularly in ocular tissues. 2,24,25 . Patients with XFS have a higher chance of converting ocular hypertension to glaucoma resulting in optic disc damage and hence a larger percentage of blindness 5 .…”
Section: Discussionmentioning
confidence: 99%